ANALISIS PENGARUH DEBT TO ASSET RATIO, DEBT TO EQUITY RATIO, DAN STRUKTUR MODAL TERHADAP RETURN ON EQUITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putra, Dori HP (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This study aims to determine the effect of debt to asset ratio, debt to equity ratio, and capital structure on return on equity in manufacturing companies listed on the Indonesian stock exchange for the period 2013-2017. This study used secondary data. The sample used was 55 manufacturing companies on the Indonesia Stock Exchange during the 2013-2017 research period. The free variables in this study are debt to asset ratio, debt to equity ratio, and capital structure. Sampling in this study used purposive sampling techniques. The data analysis methods used are classical assumption test, hypothesis testing, F test and T test. Based on the results of this study, it is known that debt to equity ratio, and capital structure have a significant influence on return on equity. While the debt to asset ratio does not have a significant effect on return on equity, the results of the F test show that the influence of debt to asset ratio, debt to equity ratio, and capital structure together t has an influence on return on equity